Assessing the Rotation of the First Metatarsal on Computed Tomography Scans: A Systematic Literature Review. (January 2022) - Najefi, Ali-Asgar; Malhotra, Karan; Patel, Shelain; Cullen, Nicholas; Welck, Matthew
Background: Hallux valgus is a multiplanar deformity that is often treated on the basis of 2-dimensional (2D) parameters and radiographs. Recurrence rates after surgical correction remain high, and failure to correct pronation of the metatarsal is increasingly stipulated as being part of the problem. Multiple methods of assessing metatarsal pronation have been proposed. Methods: We performed a systematic literature review identifying studies that measured metatarsal pronation and torsion on computed tomography (CT) scans. Specific methodology, patient groups, results, and reliability assessments were all reported. Results: We identified 14 studies that fulfilled the inclusion criteria. Eleven studies measured 2D values on CT scan, and 3 studies used computer-based 3-dimensional (3D) modeling and artificial intelligence systems to help calculate pronation. Metatarsal pronation angle, α angle, sesamoid rotation angle, and measurements for torsion were the most commonly used methods. All angles and measurements were performed as 2D measurements, but the metatarsal pronation angle was also performed with 3D modeling. Reliability and reproducibility of the α angle and metatarsal pronation angle were excellent, despite being performed on studies with small numbers. Conclusion: Multiple methods have been reported to demonstrate first metatarsal pronation on CT, of which the α angle and the metatarsal pronation angle are the most pragmatic and useful in a clinical setting. Further work is needed to further validate the reliability of these measurements in larger series and to identify normal pronation and metatarsal torsion on weightbearing imaging. Further work is required to determine whether addressing pronation reduces recurrence rates and improves outcomes in surgery for hallux valgus. Level of Evidence: Level III, retrospective cohort study.